Effects of dietary interventions on pregnancy outcomes: a systematic review and meta‐analysis. Issue 1 (22nd July 2014) - Gresham, Ellie; Bisquera, Alessandra; Byles, Julie E.; Hure, Alexis J.
Abstract: Dietary intake during pregnancy influences maternal health. Poor dietary practices during pregnancy have been linked to maternal complications. The objective was to determine the effect of dietary intervention before or during pregnancy on pregnancy outcomes. A systematic review was conducted without date restrictions. Randomised controlled trials (RCTs) evaluating whole diet or dietary components and pregnancy outcomes were included. Two authors independently identified papers for inclusion and assessed methodological quality. Meta‐analysis was conducted separately for each outcome using random effects models. Results were reported by type of dietary intervention: (1) counselling; (2) food and fortified food products; or (3) combination (counselling + food); and collectively for all dietary interventions. Results were further grouped by trimester when the intervention commenced, nutrient of interest, country income and body mass index. Of 2326 screened abstracts, a total of 28 RCTs were included in this review. Dietary counselling during pregnancy was effective in reducing systolic [standardised mean difference (SMD) −0.26, 95% confidence interval (CI) −0.45 to −0.07; P < 0.001] and diastolic blood pressure (SMD −0.57, 95% CI −0.75 to −0.38; P < 0.001). Macronutrient dietary interventions were effective in reducing the incidence of preterm delivery (SMD −0.19, 95% CI −0.34 to −0.04; P = 0.01). No effects were seen for other outcomes. Dietary interventions showed some small, but significant differences in pregnancy outcomes including a reduction in the incidence of preterm birth. Further high‐quality RCTs, investigating micronutrient provision from food, and combination dietary intervention, are required to identify maternal diet intakes that optimise pregnancy outcomes.